Topological deconfinement transition in QCD at finite isospin density - Kouji Kashiwa; Akira Ohnishi (Physics Letters B, 2017)
The confinement–deconfinement transition is discussed from topological viewpoints. The topological change of the system is achieved by introducing the dimensionless imaginary chemical potential (θ). Then, the non-trivial free-energy degeneracy becomes the signal of the deconfinement transition and it can be visualized by using the map of the thermodynamic quantities to the circle S1 along θ. To understand this “topological” deconfinement transition at finite real quark chemical potential (μR), we consider the isospin chemical potential (μiso) in the effective model of QCD. The phase diagram at finite μiso is identical with that at finite μR outside of the pion-condensed phase at least in the large-Nc limit via the well-known orbifold equivalence. In the present effective model, the topological deconfinement transition does not show a significant dependence on μiso and then we can expect that this tendency also appears at small μR. Also, the chiral transition and the topological deconfinement transition seems to be weakly correlated. If we will access lattice QCD data for the temperature dependence of the quark number density at finite μiso with θ=π/3, our surmise can be judged.